1994
DOI: 10.1016/0165-1684(94)90058-2
|View full text |Cite
|
Sign up to set email alerts
|

Morphological signal processing and the slope transform

Abstract: This paper presents the operation of tangential dilation, which describes the touching of differentiable surfaces. It generalizes the classical dilation, but is invertible. It is shown that line segments are eigenfunctions of this dilation, and are parallel transported, and that curvature is additive. We then present the slope transform which provides tangential morphology with the analytical power which the Fourier tansform lends to linear signal processing, in particular: dilation becomes addition (just as u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 5 publications
0
55
0
Order By: Relevance
“…It is well-known that any linear shift-invariant system can be described as a convolution that can be computed elegantly as multiplication in the Fourier domain [40,46]. On the other hand, morphological systems are based on erosions (or dilations) with a concave structuring function, which comes down to additions in the slope domain [42,16]. An explanation for the quasi-logarithmic connection between both worlds has been obtained by Burgeth and Weickert [12]: While linear system theory uses the classical algebra (R, ·, +), they showed that mathematical morphology is a system theory in the min-plus algebra (R ∪ {+∞}, +, min).…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that any linear shift-invariant system can be described as a convolution that can be computed elegantly as multiplication in the Fourier domain [40,46]. On the other hand, morphological systems are based on erosions (or dilations) with a concave structuring function, which comes down to additions in the slope domain [42,16]. An explanation for the quasi-logarithmic connection between both worlds has been obtained by Burgeth and Weickert [12]: While linear system theory uses the classical algebra (R, ·, +), they showed that mathematical morphology is a system theory in the min-plus algebra (R ∪ {+∞}, +, min).…”
Section: Introductionmentioning
confidence: 99%
“…Interest in mathematical morphology has grown enormously during the past decade and our understanding of the underlying mathematical structure has improved beyond measure. Nevertheless, it is only since 1993 that the existence of a transform that maps the basic morphological operation into a simpler "product", just as the Fourier transform maps the convolution product into a direct product, has been known [14][15][16][17][18][19]. Furthermore, this is no mere abstract development awaiting applications.…”
Section: Multi-resolution Transformsmentioning
confidence: 99%
“…Furthermore, this is no mere abstract development awaiting applications. Dorst and van den Boomgaard [17] show that image formation in near-field microscopes is intimately related to this new transform; an article by Bonnet et al. [20] [21].…”
Section: Multi-resolution Transformsmentioning
confidence: 99%
“…Although morphological operations are straightforward in their spatial processing, more investigations are required to further find out how the structuring element is changing the original surface, just like the way that the weighting function is changing the frequency components of the surface data in a convolution operation. In this paper, we post our initial investigation on the slope transform, based on the work of Dorst and van den Boomgaard (1994) and Maragos (1995). It will be shown that the slope transform can provide an analytical ability for morphological operations, as is the Fourier transform to convolution operations in linear theory.…”
Section: Introductionmentioning
confidence: 99%